Leadership Styles And Job Performance: The Roles Of Psychological Empowerment And Person-Supervisor Fit - Lee, Ching Hoe (2018)
This research examined the relationship between leadership styles and job performance. In addition, the research proposed psychological empowerment mediates the above relationship. The research also proposed person-supervisor fit moderates the relationship between leadership styles and psychological empowerment where the positive relationship is stronger when the person-supervisor fit is higher. The research setting in which hypotheses were tested is MNCs operating in Malaysia, specifically the top three industrial states in Malaysia, namely Selangor, Penang and Johor. Examining leadership styles (transformational, transactional and laissez-faire) in MNCs is particularly useful for extending research on job performance because of the complexity of such setting highlights the importance of leaders (supervisors) and followers (employees) relationship on job performance. Additionally, many MNCs rely on teams to carry out much of their work, making the person-supervisor fit and psychological empowerment important issues for multinational management research. Using multisource data, the research found that transformational leadership has a significant positive effect on psychological empowerment. However, there is no evidence of significant effect for transactional leadership and laissez-faire on psychological empowerment. Psychological empowerment mediated the relationship between leadership style (transformational and transactional) and job performance. The results also indicated that person-supervisor fit moderates the relationship between transformational leadership and psychological empowerment, such that it strengthens the positive relationship.